Pembangunan Sistem Informasi Manajemen Inventory pada PT Total Bangun Persada dengan Menggunakan Teknologi Webbase - Kevin Septianzah (Universitas Indraprasta PGRI Jakarta, 2019)
PT Total Bangun Persada is a company engaged in construction. To improve the competitiveness of companies related to inventory management, the company must have a maximum system. Problems that are often faced related to inventory management, the absence of a system that regulates inventory in terms of lending and ordering goods and processing of goods data both in terms of borrowing and ordering are still less effective and efficient. To solve the above problems, researchers conduct data collection methods, analysis, interviews, literature reviews, and build prototypes. The approach that will be used by applying object oriented techniques is object oriented analysis, object oriented design, object oriented programming. The results of this study are inventory management information systems and it can be concluded that with the inventory management information system, it is expected that more advanced companies and more effective and efficient performance